EFFECTIVE TEACHING STRATEGIES FOR ADULT ENGLISH LEARNERS - G’ayibberdiyeva Yulduzxon Adhamjon kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This paper examines effective strategies for teaching English to adult learners by focusing on their learning characteristics, motivation, and practical needs. Adult learners bring valuable life experience and clearly defined goals to the learning process, which requires instructional approaches that are relevant and learner-centered. The study emphasizes the importance of andragogical principles, communicative language teaching, and the integration of technology in adult English education. Attention is also given to the role of motivation and the creation of a supportive psychological environment. The findings suggest that combining real-life communication tasks, learner autonomy, and technology-enhanced instruction leads to improved engagement, confidence, and practical language proficiency among adult learners.